What's my Name and other stories - Solarin Babatunde (Literamed Publications Ltd, 2004)
This collection of three hilarious short stories typifies African cultural beliefs and value system. In the Title story, What's my Name?, the traditional culture of stprytelling in the evening after dinner is captured by a group of young children. The children wind their stories around the meaning of the names they bear.
Keywords: Tales / Folk / Storytelling